The Role of Female Factory Workers in Children's Moral Education (A Case Study in RW O4 Ketitang Village, Boyolali) - Nurhadi; Rahmawati, Fira Nisa (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to describe the role of female factory workers in children's moral education, as well as supporting and inhibiting factors in the implementation of moral education for children. This research is qualitative research. Interviews and observation are the data collection methods used. The subjects of this study are four women as mothers, with the criteria of working as factory workers in RW 04 Desa Ketitang, Nogosari, Boyolali. The results of this study indicate that the role of female factory workers in providing moral education for children in RW 04 Desa Ketitang is to provide examples, advice, and habituation. The supporting factors are: family support, the establishment of TPQ in Desa Ketitang, and a good community environment. The inhibiting factors are the lack of religious knowledge by female factory workers and the two roles played by female factory workers. However, it is very important for a mother to provide moral education to children.